A Hotspot in the Romanian Black Sea: Eelgrass Beds Drive Local Biodiversity in Surrounding Bare Sediments - Surugiu, Victor; Teacă, Adrian; Şvedu, Ilie; Quijón, Pedro A. (Frontiers in Marine Science, 2021)
Ecosystem engineers create habitat and provide conditions otherwise unavailable for the development of diverse communities. In marine soft-bottoms in particular, the biodiversity sustained by a matrix of relatively uniform sediments can be drastically enhanced by the presence of ecosystem engineers such as seagrasses. Unfortunately, the influence of seagrass meadows on the diversity of surrounding sediments is often unrecognized in spite of its importance, especially in coastlines exposed to multiple sources of pollution. This study examined composition and diversity associated with a bed of Zostera noltei Hornemann, 1832, and its surrounding bare sediments in a highly urbanized coastal area of the Romanian Black Sea. Dissimilarity levels were quantified and key species driving the differences between uniform (bare) and complex (eelgrass) sedimentary habitats were identified. 48 taxa were collected and counted, with epifaunal and infaunal species each accounting for nearly half of that diversity. Abundance, richness and diversity were strikingly higher in eelgrass-associated sediments, a difference driven primarily by various species of snails, crustaceans, polychaetes and bivalves. Between-habitat differences remained significant even after the removal of epifaunal species and each dataset undergoing strong data transformation. These results suggest that even small eelgrass beds, located in the vicinity of multiple sources of stress, can act as hotspots and make a substantial contribution to local benthic diversity.